Assessing the Impact of Open Banking Initiatives on E-Service Quality in Saudi Arabia: A Quantitative Study - Alsuhaimi, Majed Salem (European Journal of Sustainable Development, 2025)
This study investigates the impact of open banking initiatives on e-service quality in Saudi Arabian banks. Using a quantitative approach, we surveyed 513 bank customers to assess changes in perceived e-service quality following the implementation of open banking. The study employs an extended E-S-QUAL model, incorporating dimensions specific to open banking. Results indicate that open banking initiatives significantly enhance e-service quality, particularly in the areas of efficiency, system availability, and innovation. However, challenges remain in privacy and security perceptions. This research contributes to the understanding of technology-driven banking innovations in emerging markets and provides practical implications for banks and regulators in Saudi Arabia and similar contexts. Keywords: open banking, e-service quality, Saudi Arabia, financial technology, E-S-QUAL